Multiple cutaneous bronchogenic cysts located on the neck and the scalp - Khaled, Aida (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2008)
Bronchogenic cyst is a benign congenital developmental abnormality of the embryonic foregut. The skin is a rare site for bronchogenic cysts, and in thislocation it is often a solitary lesion. It is poorly recognized by clinicians and in almost all cases the diagnosis is established by histopathologic examination. This report documents a new case of multiple cutaneous bronchogenic cysts bilaterally located on the neck and on the scalp,which are unusual locations of this lesion.
Keywords: Adult; Bronchogenic Cyst; bronhogen ciste; Bronhogena cista; dermatologija; Kožne bolezni; kožne spremembe; Lasišče; Neck; Odrasli; Scalp; Skin Diseases; Vrat; Vrata